Police and the Prevention of Crime : Commerce, Temptation and the Corruption of the Body Politic, from Fielding to Colquhoun - Dodsworth, Francis (The British journal of criminology, 2007)
Examining the conception and legitimization of systems for the prevention of crime in eighteenth-century Britain, particularly in the work of Henry Fielding and Patrick Colquhoun, I argue that the conceptualization of the causes and effects of crime as stemming from social processes rather than individual character is central to the history of the social. Examination of the work of eighteenth-century theorists of police demonstrates a particular understanding of links between economic, social and political change. Fielding and Colquhoun argued that crime was a public problem because, through imitation, vice spread like disease throughout the body politic, corrupting the state and leaving it weak and liable to dissolution. To prevent crime was to prevent corruption spreading by removing temptations into vice